Development rates, larval survivorship and wing length of culex pipiens (Diptera: Culicidae) at constant temperatures - Loetti, María Verónica (2011)
In this study, the effects of rearing temperature on survival and development rate of pre-imaginal stages and on wing length of adult Culex pipiens (Diptera: Culicidae) were evaluated. Larvae I were reared until adult emergence at seven constant temperatures between 7 and 33°C. The highest survival was found at 25°C. The development rate of the immature stages decreased with increasing temperature until 30°C. The threshold temperature and thermal constant were, respectively, 5.2°C and 186.5 degree-days for males, and 5.5°C and 199.5 degree-days for females. According to a non-linear model, the lower and upper thermal thresholds were, respectively, 8.4°C and 34.4°C for males, and 9.8°C and 34.2°C for females. Wing length decreased with increasing temperature. Wings of females were longer than those of males. This study showed that survival and development of immatures and adult size were affected by rearing temperature. In addition, results suggest that this effect may differ between sexes.